-2=5x-x-2

Simple and best practice solution for -2=5x-x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2=5x-x-2 equation:


Simplifying
-2 = 5x + -1x + -2

Reorder the terms:
-2 = -2 + 5x + -1x

Combine like terms: 5x + -1x = 4x
-2 = -2 + 4x

Add '2' to each side of the equation.
-2 + 2 = -2 + 2 + 4x

Combine like terms: -2 + 2 = 0
0 = -2 + 2 + 4x

Combine like terms: -2 + 2 = 0
0 = 0 + 4x
0 = 4x

Solving
0 = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
0 + -4x = 4x + -4x
Remove the zero:
-4x = 4x + -4x

Combine like terms: 4x + -4x = 0
-4x = 0

Divide each side by '-4'.
x = 0

Simplifying
x = 0

See similar equations:

| 3=-2x+6x+7 | | p=44/9(20) | | p=44/9(18) | | -89=6x+2x-9 | | 2/5+2x=-28/5 | | 12-12z=-9-10 | | p-36=44/9(h-6) | | 18u^6-8u^4/2u^3 | | h=-16t^2+64t+720 | | Z=12 | | 25+24z=25+25z | | 60x-0.2x^2=p(x) | | 45+9y=90 | | -18=-3/5w | | 2v=-14/9 | | 6.5/3X+5=111/2 | | -3.9+m=-3.9 | | 2v=14/9 | | z^2-iz+12=0 | | 60-2P=-20+4P | | -7x=-3x-12 | | 3+7x=12-12x | | 14d+9=6d+25 | | 6(x-3)=-4.2 | | -2(-8u+3)-7u=5(u-1)-7 | | 8(a+1)=21.6 | | -43-3x=6-9x | | 33.7=9c-5 | | 3e-5=19.9 | | Y-23-37Y=3 | | p-18=18(h-6) | | 5x-14=16x |

Equations solver categories